Firm Innovation and Productivity in Latin America and the Caribbean The Engine of Economic Development - Inter-American Development Bank; Grazzi, Matteo; Pietrobelli, Carlo (Palgrave Macmillan US : Imprint: Palgrave Macmillan, 2016)
This volume uses the study of firm dynamics to investigate the factors preventing faster productivity growth in Latin America and the Caribbean, pushing past the limits of traditional macroeconomic analyses. Each chapter is dedicated to an examination of a different factor affecting firm productivity - innovation, ICT usage, on-the-job-training, firm age, access to credit, and international linkages - highlighting the differences in firm characteristics, behaviors, and strategies. By showcasing this remarkable heterogeneity, this collection challenges regional policymakers to look beyond one-size-fits-all solutions and create balanced policy mixes tailored to distinct firm needs.       This book is open access under a CC BY-NC-ND 3.0 IGO license.      .